My darkest years : memoirs of a survivor of Auschwitz, Warsaw and Dachau - Bachner, James 1922- (McFarland, 2007)
"Bachner's memoir is a poignant and often horrific account of Jewish struggles during the days of World War II. The end of the war, Bachner's reunion with his remaining family members and his eventual relocation to America are also discussed"--Provided by publisher